De l’apparente perpétuité des blocages politiques libanais - Barah Mikail (EchoGéo)
Will Lebanon know peace soon ? It is quite tempting to doubt it. Almost three years since the assassination of the former Prime Minister Rafiq Hariri and the withdrawal of the Syrian army, the country is still prey to internal struggle reflecting the unhealthy opportunism to which the main Lebanese political parties are attached. In such a context, is it reasonable to hope that a potential solution exists ? And if so, then which one ?